Partisipasi Pesantren Dalam Upaya Mendukung Halal Lifestyle - Ade Fartini; Afiza Zahra (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2023)
Pesantren is an Islamic educational institution that can be a model for facilitating, promoting, and empowering to mobilize the community to understand and implement the lifestyle of halal as a part of the Islamic teachings and religious awareness of doing the command from Allah SWT as stipulated in Al-Baqarah, chapter 168, chapter 173, chapter 219 and in Al-Maidah, chapter 3. The writer uses the descriptive-qualitative analysis model in this research. The importance of halal awareness is an implementation of the values of Islamic teachings. Indonesian human resources is a big halal market due to the large number of the Muslim population. The Pesantren Institution with the size of the Islamic population in which close to the community meets the requirement to be the government partner in participating, empowering, and socializing the halal lifestyle to the community, especially the llamas, kiai, Ustaz, and santri who have an outstanding understanding on Islamic teachings to propel the healthy and halal lifestyles. The guarantee on halal lifestyle usage has been stipulated through Indonesian Law No. 33, 2014 on the Halal Guaranteed Products. The halal regulation has been made and validated as a protection from the state towards its citizens.